Calidad de vida en pacientes con enfermedad periodontal Atendidos en el posgrado de periodoncia de la Universidad Antonio Nariño (2023)
Tooth loss due to periodontitis has a negative impact on people's quality of life. Once the teeth are lost, the person begins to see their function affected, dental migration inducing occlusal and articulation alterations. On a social level, he may present feelings of isolation due to difficulty in being able to communicate, in addition to aesthetic alterations and in his interpersonal relationships. Objective: To determine the quality of life related to oral health in patients diagnosed with periodontal disease in the periodontics postgraduate course of the Antonio Nariño University, second semester 2022 and first semester 2023